2012
DOI: 10.1007/s00436-012-2869-y
|View full text |Cite
|
Sign up to set email alerts
|

Saliva and sera IgA and IgG in Egyptian Giardia-infected children

Abstract: Giardiasis is a gastrointestinal infection of wide distribution that is more prevalent in childhood. Easy and rapid diagnosis of giardiasis is essential for reduction of this infection. This cross-sectional study included 62 children in which collection of saliva, stool and serum samples was performed. An enzyme-linked immunosorbent assay (ELISA) technique was evaluated to detect IgA and IgG responses in both saliva and serum samples. Twenty-two children were positive for Giardia duodenalis infection by direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
1
15
1
Order By: Relevance
“…Studies have suggested that anti-Giardia IgA antibody is a better indicator of current infection than IgG, since it is predominantly produced in the gastrointestinal tract [15,16]. However, the seroprevalence of IgA in our study was higher than that of IgG (23.6% vs. 13.9%).…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Studies have suggested that anti-Giardia IgA antibody is a better indicator of current infection than IgG, since it is predominantly produced in the gastrointestinal tract [15,16]. However, the seroprevalence of IgA in our study was higher than that of IgG (23.6% vs. 13.9%).…”
Section: Discussioncontrasting
confidence: 85%
“…The considerable frequency of G. duodenalis and other protozoa observed in this study may be explained, in part, by the small size of the cysts, which facilitates their passage through filters and enables their escape from the standard processes of water treatment, in addition to the poor hygiene habits and immune defense immaturity of children [29]. Experimental, clinical, and epidemiological observations indicate that G. duodenalis stimulates an immune response in the host [30,31], and anti-Giardia antibodies have been detected in individuals with G. duodenalis infection [15,16]. Based on these findings, serological tests were developed to detect specific IgG, IgM, and IgA in the serum of patients.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The protective and clearance capacity of IgA during giardiasis has been investigated. Anti‐ Giardia secretory IgA can be detected in human saliva and breast milk . Mice deficient in antibody production, mainly of type IgA, fail to eliminate G. muris and G. lamblia .…”
Section: Host Defence Mechanisms Against Giardia Lambliamentioning
confidence: 99%
“…Salivary (IgA) and serum (IgG) responses against G. duodenalis infection were significantly higher in infected patients than in controls. This observation could lead to the development of a diagnostic tool that measures specific salivary IgA and specific serum IgG antibodies to monitor the exposure of various populations to G. duodenalis . Therefore, B cells and especially IgA antibodies are important but not strictly required for the control of Giardia infections.…”
Section: Host Defence Mechanisms Against Giardia Lambliamentioning
confidence: 99%